Impaired Upregulation of the Costimulatory Molecules, CD27 and CD28, on CD4(+) T Cells from HIV Patients Receiving ART Is Associated with Poor Proliferative Responses. - Tanaskovic, S.; Price, Patricia; French, M.; Fernandez, S. (Mary Ann Liebert, Inc., 2016)
HIV patients beginning antiretroviral therapy (ART) with advanced immunodeficiency often retain low CD4(+) T cell counts despite virological control. We examined proliferative responses and upregulation of costimulatory molecules, following anti-CD3 stimulation, in HIV patients with persistent CD4(+) T cell deficiency on ART. Aviremic HIV patients with nadir CD4(+) T cell counts <100 cells/µL and who had received ART for a median time of 7 (range 1-11) years were categorized into those achieving low (<350 cells/µL; n?=?13) or normal (>500 cells/µL; n?=?20) CD4(+) T cell counts. Ten healthy controls were also recruited. CD4(+) T cell proliferation (Ki67) and upregulation of costimulatory molecules (CD27 and CD28) after anti-CD3 stimulation were assessed by flow cytometry. Results were related to proportions of CD4(+) T cells expressing markers of T cell senescence (CD57), activation (HLA-DR), and apoptotic potential (Fas). Expression of CD27 and/or CD28 on uncultured CD4(+) T cells was similar in patients with normal CD4(+) T cell counts and healthy controls, but lower in patients with low CD4(+) T cell counts. Proportions of CD4(+) T cells expressing CD27 and/or CD28 correlated inversely with CD4(+) T cell expression of CD57, HLA-DR, and Fas. After anti-CD3 stimulation, induction of CD27(hi)CD28(hi) expression was independent of CD4(+) T cell counts, but lower in HIV patients than in healthy controls. Induction of CD27(hi)CD28(hi) expression correlated with induction of Ki67 expression in total, naïve, and CD31(+) naïve CD4(+) T cells from patients. In HIV patients responding to ART, impaired induction of CD27 and CD28 on CD4(+) T cells after stimulation with anti-CD3 is associated with poor proliferative responses as well as greater CD4(+) T cell activation and immunosenescence.